KAJIAN DAMPAK BENCANA LAHAR DINGIN PASCA LETUSAN GUNUNGAPI MERAPI TERHADAP KETAHANAN SOSIAL EKONOMI (Studi Kasus Desa Jumoyo, Kecamatan Salam, Kabupaten Magelang, Provinsi Jawa Tengah) - , Diah Arifika ([Yogyakarta] : Universitas Gadjah Mada, 2012)
On december 5, 2011, it was the beginning of the lahar disaster which hitting Gempol area of Jumoyo Village. The disaster led to the destruction mostly land use designated as residential areas, agriculture, fisheries and business sites. As result of the disaster was about 157 families were relocated from Gempol area to temporary shelter (Huntara) since April 2011. The objectives of this study were (1) to determine the changes of victims' welfare caused by the lahar disaster (2) to determine implications of the welfare changes in socio-economic resilience of the Gempol community. The used method was survey, by direct interview toward respondents through questionnaire as a means of collecting data on the welfare changes pre- and post- lahar disaster. The determination of the respondents in the study was obtained by random sampling method. Respondents sampled in this study were the head of the family on Gempol village totaled 50 respondents. From the research results, it was occurred a welfare change. Declining of economic conditions was characterized by changes of livelihoods. On predisaster, the majority of population (42% of respondents) worked as farm-laborer, and post-disaster, about 38% respondents worked as sand-laborer, on pre-disaster, about 64% respondents had income> Rp 500.000,00 and after-disaster, 56% respondents had income <Rp 500.000,00 On pre-disaster, about 44% respondents had a total expenditure> Rp 500.000,00 and after-disaster, about 84% respondents had expenditure<Rp 500.000,00. The changes in social conditions marked by declined quality of health care, declined educational achievement and social interaction is weakened. Such decreased welfare had implications on lower socioeconomic resilience for disaster-affected communities those staying in the shelters.